The Webb Law: Its Scope and Operation - Notz, William (Journal of Political Economy, 1919)
In connection with the lively interest displayed by American business men in the new situations which have developed in international trade as a result of the world-war, the so-called Webb law is receiving a noticeable share of attention. Excluding all merely temporary, war-time legislation, it is the most important piece of legislation enacted by Congress during the war for the promotion of American export trade. Together with the Federal Reserve Act, and the act authorizing the War Finance Corporation to furnish credits to finance foreign trade, the Webb law represents a noteworthy forward step in the consummation of an American foreign-trade policy. Already a literature of considerable volume has grown up on the Webb Act, and one of our large law schools has included a study of this law in one of the courses of its curriculum. Moreover, interest in the Webb law is not confined exclusively to this country. The provisions of the Act and its operation have been the subject of numerous articles in foreign publications. With one or two exceptions, which will be noted further on, the comments on the law which have appeared in the foreign press have not voiced any unfavorable criticism. On the contrary, the Act has been pointed to as a model statute.